Effect of Hydration and Oxidation Reactions of The Chemical Composition of Kaffir lime (Cytrus hystrix DC.) Oil - Warsito Warsito; Edi Priyo Utomo; Siti Mariyah Ulfa (The Journal of Pure and Applied Chemistry Research, 2016)
This research aims to determine changes of  the chemical composition in the hydration and oxidation reaction of Kaffir lime (Cytrus hystrix DC.) oil. The hydration reaction was carried out using a Amberlyst catalyst with variation time for 1.5, 3, and 4.5 hours. Furthermore, the oxidation process was carried out using PCC catalyst with variation time for 1, 1.5, and 3 hours. Then, the analysis of chemical composition was performed using GC-MS. The results showed that hydration reaction process for 1,5 hours has changed monoterpenes micrene and b-ocimen turned into linalool and it changes citronellal to be linalool, citronellol and dimer ether citronellyl citronellol. The longer process of hydration tends to increase the dimer ether citronellyl citronellol products. Within that process, it has turned citronellal into isopulegol and isopulegone. The longer oxidation will decrease  isopulegone products.